Copyright Questions and Answers for Information Professionals - Laura N. Gasaway (Purdue University Press, 2013)
For almost 15 years I have authored the â€œCopyright Questions and Answersâ€ column for Against the Grain (ATG). It has been a labor of love, and I very much enjoy responding to the questions that librarians, publishers, teachers, and authors raise in my copyright law workshops, submit to me over the telephone, and increasinglyâ€”today almost exclusivelyâ€”send to me via e-mail. I was delighted when Katrina Strauch asked me to turn questions from this column into a book that the journal would publish as the first in a series of books evolving from ATG. She was fortunate to strike an agreement with Purdue University Press to publish the series. I have always felt a responsibility to respond to questions, hoping that I could help fellow librarians and faculty members who struggle to comply with copyright law and have nowhere to go for help. Who knew that these questions would lead to, first of all, the creation of the ATG column, and now this book. My own interest in copyright for librarians and teachers is long and deep. I completed my MLS in 1968 and worked as a librarian in the University of Houston Law Library while I simultaneously attended law school there. In 1973, as I was about to receive my JD degree, Williams & Wilkins Co. v. United States,1 was affirmed in a per curiam opinion from an evenly divided U.S. Supreme Court. The first library photocopying case involved a medical publisher suing the National Library of Medicine for photocopying for medical researchers from the publisherâ€™s journals. I felt as if my eyes had been opened, and I knew how I would spend my careerâ€”educating librarians, college faculty, and Kâ€“12 teachers about copyright. The ATG column is a part of this outreach.